Perkembangan Sosial Emosional pada Anak Usia 5-6 Tahun dan Keterlibatan Orang Tua di TK Harun Ar-Rasyid - Elsya Nadia; Sahara Sahara; Thaibah Tunnisa Mufti Sirait; Adhila Adhila; Khadijah Khadijah (CV. KAMPUS AKADEMIK PUBLISING, 2025)
This study aims to examine the socio-emotional development of early childhood through observation and interviews at TK Harun Ar-Rasyid. Socio-emotional development is a crucial aspect of character formation and children's readiness for further education. The research method used is descriptive qualitative, employing direct observation, teacher interviews, and assessment instruments based on socio-emotional development indicators. The findings reveal that most children at TK Harun Ar-Rasyid have shown good progress in recognizing and expressing emotions, forming social relationships, and cooperating with peers. Teachers' roles and parental involvement significantly influence this development. However, challenges remain, such as inconsistent parenting patterns and limited parental time. Therefore, stronger collaboration between the school and families is necessary to create a supportive environment for the socio-emotional development of early childhood.